Two components of delayed rectifier K^＋ current in heart： molecular basis, functional diversity, and contribution to repolarization - Cheng, Jian-hua; Kodama, Itsuo (Acta pharmacologica Sinica, 2004)
Delayed rectifier K^+ current (IK) is the major outward current responsible for ventricular repolarization. Two components of IK (IKr and/Ks) have been identified in many mammalian species including humans. IKr plays a pivotal role in normal ventricular repolarization. A prolongation of action potential duration (APD) under a variety of conditions would favor the activation of IKs so that to prevent excessive repolarization delay causing early afterdepolarization. The pore-forming α subunits of IKr and IKs are composed of HERG (KCNH2) and KvLQT1(KCNQ1), respectively. KvLQT1 is associated with a function-altering β subunit, minK to form IKs. HERG may be associated with minK (KCNE1) and/or minK-related protein (MiRP1) to form IKr, but the issue remains to be established. IKs is enhanced, whereas IKr is usually attenuated by β-adrenergic stimulation via cyclic adenosine 3',5'-monophosphate (cAMP)/protein kinase A-dependent pathways. There exist regional differences in the density of IKr and IKs transmurally (endo-epicardial) and along the apico-basal axis, contributing to the spatial heterogeneity of ventricular repolarization. A decrease of IKr or IKs by mutations in either HERG, KvLQT1, or KCNE family results in inherited long QT syndrome (LQTS) with high risk for Torsades de pointes (TdP)-type polymorphic ventricular tachycardia and ventricular fibrillation. As to the pharmacological treatment and prevention of ventricular tachyarrhythmias, selectively block of IKs is expected to be more beneficial than selectively block of IKr in terms of homogeneous prolongation of refractoriness at high heart rates especially in diseased hearts including myocardial ischemia.